Ether, the old quantum theory, philosophy of nature and the problem of continuity as defined by Bogdan Szyszkowski: Contribution to research on the reception of the old quantum theory and quantum mechanics in Poland before 1953 - Mścisławski, Łukasz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2020)
The aim of this paper is to present the views of one of prominent Polish chemists, namely Bohdan Szyszkowski. Presented views are concerning the relation of the concepts of aether, continuity and causality in the context of revolution in physics that took place at the turn of 19th and 20th centuries. The issues particularly concern his thoughts related to the old quantum theory and special relativity. In particular, this article presents the role of these concepts in the foundations of physics and – in a more general aspect – in the recognized fields of knowledge. The nature of Szyszkowski’s analysis allows him to be considered a very interesting thinker in the area that today is called the philosophy of physics or, perhaps more accurately, the philosophy in science. An important observation made by Szyszkowski is emphasized that mathematical structures cannot have physical properties. Attention was also paid to the Polish intellectual community, which was formed in Kiev before 1919.